The Impact of Public Government Spending on Public Debt in the Iraqi Economy - Alhamdany, Saad Noori; Alhamdany, Mohammed Noori; Obed, Muhannad Khalifa; Alhamdany, Saba Noori (International Journal of Economics and Financial Issues, 2025)
Nations that depend intensely on external incomes, such as oil, and lack income broadening, financial changes, or a decrease in product costs, may resort to increased borrowing to cover money-related shortfalls. The investigation aims to illustrate the effect of the relationship between government investment and open obligation in Iraq by measuring this relationship and knowing the extent to which government investment impacts both residential and outside obligations. The study reveals a reverse relationship between venture investing and household obligations, a converse relationship between customer investing and external obligations in the short term, and a reverse relationship between them in the long term. The study also suggests that significant progress should be made in improving investing proficiency. The focus should be on enhancing the proficiency of government investing, eliminating waste and degradation, coordinating investments towards ventures with high financial and social returns, broadening sources of revenue, lessening dependence on a single source of salary such as oil, and expanding financial diversity.